Anesthesia in Parathyroidectomy for Secondary Hyperparathyroidism of Chronic Kidney Disease - ZHANG Yangyang; ZHU Bo (Xiehe Yixue Zazhi)
With the increasing prevalence of chronic kidney disease, the incidence of renal secondary hyperparathyroidism (SHPT) has also reached a high level. At the beginning of the course of SHPT, medical treatment is the main method, but nearly 10% of patients eventually need to undergo parathyroidectomy. The perioperative management of such operations requires comprehensive consideration of the influence of primary disease, secondary pathophysiological changes and surgical factors, which poses a challenge to anesthesiologists. This article summarizes the pathophysiological characteristics, treatment status and anesthesia points of SHPT, with the aim of providing reference for the implementation of safer and better anesthesia management for SHPT patients.